REQUISITOS PARA A CONCESSÃO DA JUSTIÇA GRATUITA E A GARANTIA DE ACESSO À JUSTIÇA DO TRABALHO (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2023)
The guarantee of broad access to justice consists in the swift, adequate, effective and full access to the citizen. The recognition of the possibility of granting free justice to the individual employer, with unequivocal proof of his state of hyposufficiency, by art. 2nd, § 1st, of Resolution no. 66/2010, of the CSJT, and the majority understanding of the TST and STJ, is an important advance. Furthermore, the Federal Supreme Court has recently tackled the issue. Through the methodology of the bibliographic review, the present study aims to study the necessary requirements for the granting of free justice to the individual employer, based on recent doctrinal and jurisdictional understandings on the subject.